#### Answer

4$(8g^{2}+5h^{3})(8g^{2}-5h^{3})$

#### Work Step by Step

We use the formula for the difference of squares to apply to this question.
The difference of squares formula is:
$(a-b) (a+b) = a^{2} - b^{2}$
= 4($64g^{4}$ - $25h^{6}$)
*** Take the square root of $64g^{4}$ which is $8g^{2}$. Becuase $8g^{2}$ × $8g^{2}$ = $64g^{4}$
*** Take the square root of $25h^{6}$ which is $5h^{3}$. Becuase $5h^{3}$ × $5h^{3}$ = $25h^{6}$
= 4($(8g^{2})^{2}−(5h^{3})^{2}$)
In the given formula let $8g^{2}$ represents a and $5h^{3}$ represents b.
4($(8g^{2})^{2}−(5h^{3})^{2}$) = 4$(8g^{2}+5h^{3})(8g^{2}-5h^{3})$